The Effect of STAD-based QuizWhizzer on Students' Cognitive Learning Outcomes and Anthusiasm on Circulatory System - Fania, Aura Titis; Hadiyanti, Lutfia Nur (Journal of Biology Education, 2025)
Learning activities are activities carried out by students and require them to play an active role during the activity. Based on the results of interviews and observations, it is known that student participation in discussions at SMAN 1 Ungaran is still low, this has a negative impact on understanding the material of the human blood circulation system. The integration of QuizWhizzer in the STAD model can be a solution to the problem by supporting student interactivity in learning. This study aims to analyze the effect of QuizWhizzer in the Student Teams-Achievement Division (STAD) model on students' cognitive learning outcomes on the material of the blood circulation system. The research method used Quasy Experiment Non-Equivalent Control Group Design. The results of posttest analysis with Independent sample T-test and Paired Sample T-test showed Sig. (2-tailed) 0.017 and 0.000 which means there was a significant increase in the cognitive learning outcomes of experimental class students compared to the control class, with an average posttest score of 83.8 experimental class and 79 control class. Thus, QuizWhizzer in the STAD model has an effect on improving students' cognitive learning outcomes on the material of the human blood circulation system. This combination is able to create an interesting and fun learning atmosphere, and is recommended to be applied to various other subjects.